Developing a fuzzy Topsis decision-making model to select the optimal place to buy real estate in Tehran from an investor's point of view. - Saeid Karimi (مهندسی و مدیریت ساخت)
Abstractthe purpose of this paper is fuzzy multi-criteria decision-making models topsis to select the optimal location from the perspective of the investor is buying real estate in the city of Tehran, Survey and functional. The study population to real estate experts and scholars in Tehran and the number of 20 experts elected, therefore, research is acceptable reliability, The fuzzy topsis method (F Topsis) was used to evaluate and determine the weight of each criterion and sub-criteria and ranking of the studied areas in Tehran., Analysis of the data shows that among the criteria affecting the selection of optimal location in Tehran from buying real estate investors view as follows: 1) The measure social, 2) cultural and economic criteria. 3) Access and land situation, 40 physical criterion, and 5) environmental standard measure of space - performance matter most. The results are consistent with the findings of Ahmadpur and Rasaiian (1385), H. Sinai and colleagues (1393), Mahmoud Samadi et al (1394), and Deng Yi (2002), The results shows that, among different regions of Tehran (Zone 2, Zone 5, Zone 6) According to the criteria for selecting the optimal location of the property investment perspective, Region 2 in the first place, region 5, the second and third place ranking in the 6th district.